Study Anatomy of Vertebrae Caudalis Asiatic Water Monitor (Varanus salvator) - Rakhmiyati; Luthfi, Muhammad Jafar (Proceeding International Conference on Science and Engineering, 2020)
Asiatic water monitor lizard (Varanus salvator) is a type of reptile that can be found in several countries on the Asian continent. In Indonesia this species can be found in the Sunda plain (Java, Bali and Nusa Tenggara) and Maluku (the Sula and Obi islands). Asiatic water monitor lizard is long tailed reptile. The functions of tail as a movement aid, to maintain balance, a place to store energy, sexual appearance, and reproduction. The caudalis vertebrae in asiatic water monitor lizard (Varanus salvator) has a structure consisting of centrum, processus, cotyle, condilus, and constriction area. To observe the caudal vertebrae in monitor lizards the experiment was done by cleaning all the sticky tissue, then observed using a stereo microscope with a magnification of 0.8X. The result showed that blood vessels and nerve tissue were protected by sturdy bones.